HPV 16 Is Related to the Progression of Cervical Intraepithelial Neoplasia Grade 2: A Case Series - Loffredo D'Ottaviano, Maria Gabriela (Hindawi Publishing Corporation, 2013)
Purpose. To describe the acquisition, persistence, and clearance of HPV infection in women with CIN 2 followed up for 12 months. Methods. Thirty-seven women with CIN 2 biopsy, who have proven referral to cervical smear showing low-grade squamous intraepithelial lesions or atypical squamous cells of undetermined significance and tested for HPV, were followed up for one year with cervical smear, colposcopy, and HPV test every three months. HPV DNA was detected by the polymerase chain reaction and genotyping by reverse line blot hybridization assay. Results. CIN 2 regression rate was 49% (18/37), persistence as CIN 1 or CIN 2 was 22% (8/37), and progression to CIN 3 was 29% (11/37). Multiple HPV types were observed at admission in 41% (15/37) of cases. HPV 16 was detected at admission in 58% (11/19) of the cases that persisted/progressed and in 39% (7/18) of the cases that regressed. HPV 16 was considered possibly causal in 67% (10/15) of the cases that persisted or progressed and in 10% (1/10) of the cases that regressed (P = 0.01). Conclusion. Multiple HPV infections were frequently detected among women with CIN 2 at admission and during the followup. The CIN 2 associated with HPV 16 was more likely to persist or to progress to CIN 3.